Benennung und umbenennung personennamen in interkultureller kommunikation: rechtschreibfehler als umbenennung in der deutschen ubersetzung von things fall apart und arrow of God von Chinua Achebe (2015)
Personal proper names are often treated as mere ‘defining labels’ lacking in meaning, whose translation is a smooth process of transference that requires no serious decision-making process. This assumption in many extant studies quite often leads to a less adequate attention paid to their translations and, therefore, their full importance and significance in, especially narratives, are not emphasized in the target text. Employing textual and translation analyses and illustrating with purposively selected text units from the German translations of Chinua Achebe’s novels, Things Fall Apart and Arrow of God, this paper argues that personal proper names are meaningful beyond being mere referents. They are not only part of the cultural universe of a source text, especially an African cultural source text, they are also an important part of the cultural plot and can bear multiple shades of meanings. Close attention must, therefore, be paid to their orthography in the transference process of translation, in order to adequately render them into the target text in intercultural narrative communication contexts.